PENGARUH FAMILY CONTROL TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN PADA SEKTOR PERTAMBANGAN - Thadete, Natalia Brenda E. (Business Accounting Review, 2014)
In the previous studies it was found that family control was able to improve profitability, but on the other side family control was able to reduce firm value. There is a dilemma in applying family control and also the number of family firms in Indonesia encouraged the research to be conducted. The study was conducted on companies in the mining sector during the period 2009-2011. This study used quantitative approach by using regression analysis. The variables used were ROA, Tobinâs Q, firm size, sales growth, and leverage.The result of this study concluded that family control has no significant affect on profitability, but had significant negative affect on firmâs value. This study also found that firm size has positive affect on profitability and firmâs value. There was no significant affect of sales growth and leverage on profitability and firmâs value.